PENGARUH PERMINTAAN ALAT PEMBAYARAN NON TUNAI TERHADAP PENAWARAN UANG KARTAL (JUB) DI PROVINSI RIAU - Jorge Jorge; Isyandi B; Rosyetti Rosyetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this research is to determine and analyze the effect and significance of the debit card/ATM and e-money against the money supply in Riau province. The data used in this research is time series secondary data. The analytical method used is multiple linear regression analysis with the Error Correction Model (ECM) technique which aims to find the long-term and short-term balance regression equation and whether or not a model is consistent between the independent and dependent variables studied and calculated using E-views application software 10. The results showed that debit cards and electronic money had no and significant effect on money supply in the long and short term.Keywords: Debit card, e-money and money supply